Waste handling model based on local wisdom system in Indonesia - Agnes Widiyanto; Siwi P.M. Wijayanti (AOSIS, 2023)
The population of Banyumas Regency, Indonesia is around 1,620,918 people in 2018, waste production in Banyumas Regency is large and increases from year to year. Waste production in this district reaches 1,100 m3 per day. The purpose of this study is to evaluate the development model of waste management through improving the local wisdom system in Indonesia. The method used in this study is a qualitative research method to understand the phenomena experienced by research subjects holistically. This model consists of data collection, data reduction, data presentation, and withdrawal. Research instruments used are the researchers as the main instrument (human instrument), interview guidelines, check list and record tool. Data validity using the source triangu‑ lation technique carried out by crossing the answer check between informants. The result of this study is that commu‑ nity empowerment in waste management is very important. The local wisdom model in the community which is identified in this study is the existence of community empowerment and the contribution of women in household waste management.